Fiber morphology of ara (Ficus Sp.) between heartwood and sapwood - Ismail, Ismanizam (2002)
The studies of fiber morphology to the Ficus Sp. are based on the TAPPI Standard. The objectives of this study are to find the different within the wood fiber at the heartwood and sapwood. The mean, the fibers of the sapwood are longer (1.71mm) than the fiber of heartwood that is 1.25mm. The fiber diameter and lumen width at the heartwood produce the value that setting lower and the other there is the same value at the heartwood. The cell wall thickness for the both part of this wood produces the same value. The runkle ratio and felting power are higher at the sapwood. It is different with coefficient of suppleness that is found that the values at the heartwood are higher. If we see all over, used of fiber from Ficus Sp. can be widening. Although, the detail study must be done before this kind of species be full used especially in the process of producing the fiber in the demand of the wood industries that based on the wood based panel, paper making and so on.